A new species of mealybug (Hemiptera: Coccomorpha: Pseudococcidae) from Tectona grandis L.f. (Lamiaceae) in southern India - Joshi, Sunil; Jose, Bindu K.; Gullan, Penny; Sajeev, T.v.; Anoop, E.v. (Zootaxa, 2020)
A new species of mealybug, Formicococcus tectonae Joshi, Bindu & Gullan sp. n., is described and illustrated based on adult females collected from teak, Tectona grandis (Lamiaceae), in plantations in Thrissur district, Kerala, southern India. The mealybug lives in tunnels made by the teak trunk borer, Cossus cadambae (Moore) (Lepidoptera: Cossidae). Ants of a Tapinoma species were found in the tunnels, tending the mealybugs. The new mealybug is most similar morphologically to F. polysperes Williams and F. robustus (Ezzat & McConnell) comb. rev. A key to adult females of all the Formicococcus species recorded from India is provided.